ГЕОМОРФОЛОГИЯ И МОРФОТЕКТОНИКА ЛЕНО-АНГАРСКОГО ПЛАТО - Уфимцев Г.Ф.; Щетников А.А.; Мяктова В.В.; Филинов И.А. (My University, 2005)
Lena-Angara plateau occupies the central part of the southern projection of Siberian platform. The young uplift of plateau has non-arched character. Its cause is the accretion of layered rock masses of platform cover, detached sub-horizontally by evaporates layers. Typta-Tutur depression has a peculiar position in the young tectonics of plateau, being the reversed-straighl morphostucture.
Keywords: 551.4.033(235.3)